The Eighteenth Century Trade between the Ships of the Hudson's Bay Company and the Hudson Strait Inuit - Barr, William (ARCTIC, 1994)
From an early stage in the history of the Hudson's Bay Company, the captains of the company's ships annually received specific instructions to make contact and trade with the Inuit of southern Baffin Island in the vicinity of the Upper and Middle Savage Islands in Hudson Strait during their annual voyages from London to the posts in Hudson Bay. Documents for a 20 year period in the mid-eighteenth century reveal that a wide range of trade goods, primarily tools and hunting weapons, was provided to each captain for this purpose. A comparison of the volume of trade goods with the probable number of Inuit involved in this trade suggests that the goods were probably thereafter disseminated through inter-group trade throughout a wide area of the Canadian Arctic. Baleen from the bowhead whale (Balaena mysticetus) represented an important item being traded by the Inuit in return, at least from 1737 until the end of the century. For the period 1737-1778 the average amount of baleen traded by the Inuit of southern Baffin Island was 1237 lb (559.7 kg), i.e., approximately the amount of baleen produced by an average adult bowhead whale. For this period the baleen from this source represented 78% of all the baleen handled by the Hudson's Bay Company. The records of the Hudson Strait trade thus provide some indication of the minimum numbers of bowheads being taken annually by the Inuit of the north shore of Hudson Strait in the eighteenth century and the amount of hunting effort being devoted to whaling.Key words: baleen, bowhead whales, Hudson Strait, trade, Inuit Depuis le début de l'histoire de la Compagnie de la Baie d'Hudson, les capitaines des navires de la Compagnie, lors des voyages annuels qui les amenaient de Londres aux postes situés dans la baie d'Hudson, recevaient des directives précises afin d'entrer en contact et de commercer avec les Inuit de la partie sud de l'île Baffin située à proximité des îles Sauvages supérieures et moyennes, dans le détroit d'Hudson. Des documents datant du milieu du XVIIIe siècle ...